2019
DOI: 10.5530/pj.2019.11.201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eurycoma Longifolia Jack (Tongkat Ali) Alcoholic Root Extract Against Oral Pathogens

Abstract: Introduction: Eurycoma longifolia jack (E.L) is a herbal medicinal plant of SouthEast Asian origin, popularly recognized as 'Tongkat Ali.' The plant roots have been scientifically proven to have many biological effects including antibacterial activity however, no previous research to date has studied the effect on oral pathogens including cariogenic bacteria. This study was done to determine the antibacterial and antifungal activities of E.L. root extract against three common oral pathogens. Material and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Alloha et al [ 11 ] study on the effects of E. longifolia Jack (Tongkat Ali) alcoholic root extract against an oral pathogen. The root of E. longifolia ethanol extract with 200 mg/mL was tested using broth microdilution and agar disk diffusion test against Candida albicans and Streptococcus mutans .…”
Section: Discussionmentioning
confidence: 99%
“…Alloha et al [ 11 ] study on the effects of E. longifolia Jack (Tongkat Ali) alcoholic root extract against an oral pathogen. The root of E. longifolia ethanol extract with 200 mg/mL was tested using broth microdilution and agar disk diffusion test against Candida albicans and Streptococcus mutans .…”
Section: Discussionmentioning
confidence: 99%
“…Eurycoma longifolia Jack Tongkat Ali roots are the most important part of the plant, many studies have shown that the root has anti-malarial, aphrodisiac, anti-osteoporosis and anti-inflammatory effects 27 . Recently many studies have proved that the ethanol extract of Tongkat Ali roots possesses antioxidant and antibacterial properties against strains B. cereus, S.aureus, S. typhi 28 and Streptococcus mutans 29 . Moreover, ethanol-based Eurycoma longifolia Jack root extract exhibited positive antifungal activity against A.fumigatus and C.albicans 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently many studies have proved that the ethanol extract of Tongkat Ali roots possesses antioxidant and antibacterial properties against strains B. cereus, S.aureus, S. typhi 28 and Streptococcus mutans 29 . Moreover, ethanol-based Eurycoma longifolia Jack root extract exhibited positive antifungal activity against A.fumigatus and C.albicans 29,30 . For the antiinflammatory activity of Eurycoma longifolia Jack root, 70% ethanol extract of E. longifolia Roots displayed anti-inflammatory effects due to the presence of phenolic acids, coumarins, triterpenoids, and terpenes.…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, known that one of the mechanisms of the antimicrobial action of alkaloids is the suppression of the pathogen cytokinesis. Polyphenols are known to play a role in the inactivation of cellular enzymes in pathogens [78,79]. More studies are, however, required to unveil more details about the mechanism of action of anti-caries bioactive compounds.…”
Section: Plant-derived Cariogenic Biofilm Inhibitorsmentioning
confidence: 99%